Virtual reality and artificial intelligence: co-creation process between consumers and firms in an area of smart cities - Ferreira, Mónica Mendes; Loureiro, S. M. C.; Pereira, H. (6th International AR VR Conference: Augmented Reality and Virtual Reality - New trends in immersive technology, 2020)
The aim of this study is twofold: provide an overview of the virtual reality and artificial intelligence conceptualization and applications and propose a framework for the consumer-firm experience process in the context of smart cities. The framework will give a novel perspective on the topic and provide theoretical contributions.